2018
DOI: 10.4062/biomolther.2016.276
|View full text |Cite
|
Sign up to set email alerts
|

YJI-7 Suppresses ROS Production and Expression of Inflammatory Mediators via Modulation of p38MAPK and JNK Signaling in RAW 264.7 Macrophages

Abstract: Chalcone, (2E)-1,3-Diphenylprop-2-en-1-one, and its synthetic derivatives are known to possess anti-oxidative and anti-inflammatory properties. In the present study, we prepared a novel synthetic chalcone compound, (E)-1-(4-hydroxyphenyl)-3-(2-(trifluoromethoxy)phenyl)prop-2-en-1-one name (YJI-7), and investigated its inhibitory effects on endotoxin-stimulated production of reactive oxygen species (ROS) and expression of inflammatory mediators in macrophages. We demonstrated that treatment of RAW 264.7 macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Overproduction of ROS and reduced antioxidant capacity can result in a redox imbalance, inducing the inflammatory response and oxidative stress eventually leading to the formation of various pathophysiological lesions [ 24 ]. Consistent with the results of previous studies [ 25 , 26 , 27 ], in this study, LPS increased ROS generation in stimulated RAW 264.7 macrophages ( Figure 2 ). Co-treatment of LPS-stimulated RAW 264.7 macrophages with white mulberry fruit extract and fractions resulted in significant reductions in ROS levels.…”
Section: Discussionsupporting
confidence: 93%
“…Overproduction of ROS and reduced antioxidant capacity can result in a redox imbalance, inducing the inflammatory response and oxidative stress eventually leading to the formation of various pathophysiological lesions [ 24 ]. Consistent with the results of previous studies [ 25 , 26 , 27 ], in this study, LPS increased ROS generation in stimulated RAW 264.7 macrophages ( Figure 2 ). Co-treatment of LPS-stimulated RAW 264.7 macrophages with white mulberry fruit extract and fractions resulted in significant reductions in ROS levels.…”
Section: Discussionsupporting
confidence: 93%
“…Then, the cells were gently washed three times with HBSS to remove excess dye solution. Finally, the fluorescence intensity was measured at an excitation wavelength of 485 nm and an emission wavelength of 520 nm after 200 µ L of HBSS was loaded into the wells [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing body of evidence indicating that the P38MAPK and JNK signaling pathway contributes to melanogenesis via colaborating to inflammatory and oxidants 26 , 27 . Reactive oxygen species (ROS) production and inflammatory mediators were suppressed when P38MAPK and JNK signaling pathway was suppressed, what is more, the current study indicated that inhibition of inflammatory response and oxidative stress could reduce melanogenesis 19 .…”
Section: Discussionmentioning
confidence: 99%